MINANGKABO DI ATAS NAGARI - Alfa Noranda (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2021)
During the 76 years of Indonesia's independence, public knew that the traditional Minangkabo form of government was Nagari. The form of government of Nagari is the smallest form of government, so what is the traditional form of government structure above the Nagari in Minangkabo. This study will answer the form of government and how to make decisions based on existing historical data, it can help answer conflicts that have sprung up in the Minang community. Minangkabo are considered as one of the ethnic groups, but historical documents say it is different. At the time of the Government of the Batavian Republic in Eastern Europe through the independent government of the Governor in Batavia and his trading partners saw Minangkabau as a traditional government that had great influence at that time. For this reason, it is necessary to search for historical information historiography and transliterate the manuscript equipped with archaeological history sources in the form of old and new maps. Based on these methods and theories, it is known that the conditions regarding Minangkabo from the view of the government of the Batavian Republic are true, Minangkabo has a government structure and a way of making decisions.